Cognitive Dissonance & Plagiarism: the Banality of Academic Dishonesty - Made Syanesti Adishesa; Ferdinand Prawiro (Journal of Educational, Health and Community Psychology, 2020)
This study attempted to apply the hypocrisy induction principle in a real-life setting, a behavioral modification method in which cognitive dissonance was invoked in order to dissuade people from certain undesirable behavior. The aim of this experiment was testing the effect of hypocrisy induction in decreasing plagiarism among students. 136 high school students in their second year were categorized into four groups (hypocrisy, commitment only, mindful only, control), and given a task in which plagiarism was made possible. The tasks submitted by the students were given a plagiarism score using a program that matches them with online articles. Data analysis showed that the hypocrisy induction did not produce a significant effect on plagiarism. 92% of participants committed plagiarism in varying levels, indicating a banality of plagiarism in the school. The implications of these results on plagiarism prevention were discussed.Â Keywords: plagiarism, hypocrisy induction, cognitive dissonance, experiment